Chemical composition, antioxidant, and antiproliferative activities of nine Chinese proso millet varieties. Issue 1 (1st January 2018) - Shen, Ruiling; Ma, Yuling; Jiang, Longbo; Dong, Jilin; Zhu, Yingying; Ren, Guixing
ABSTRACT: Interest in proso millet as a functional food is growing. However, studies on the chemical composition, antioxidant, and antiproliferative activities' differences of proso millet cultivars in China are limited. Nine Chinese proso millet varieties (five waxy varieties – S, D, N2, N4, N8 and four non-waxy varieties – J1, J3, J7, J9) were investigated. Results showed that the non-waxy varieties were significantly higher than waxy varieties in the content of amylase and resistant starch (22.95%, 0.23%, 2.02%, and 0.78%, respectively; P < .05). Lys was the first limit amino acid (AAS: 16.08%). Linolenic acid (61.74%) and oleic acid (22.16%) were the dominant fatty acids. Overall, the antioxidant content and antioxidant activities of J1 and J3 were higher than other cultivars. And, J7, J3, and J1 possessed better antiproliferative effects than other proso millet varieties. These results are anticipated to provide useful information on the development of proso millet-based functional food.